2020
DOI: 10.1111/eip.12982
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profiles of healthy siblings of first‐episode schizophrenia patients

Abstract: Aim: Cognitive deficit in psychotic illness is intensively studied, different cognitive subtypes have been suggested. In recent years, there has been an increase in the number of studies in patients with schizophrenia and their relatives searching for endophenotypes of the disease. The aim of our study was to investigate cognitive performance and cognitive subtypes in the siblings of the patients.Methods: Four groups of subjects were included: patients with a first episode of psychotic illness, the siblings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(51 reference statements)
2
2
0
1
Order By: Relevance
“…Criterion (e), impairment in affected and unaffected family members at a higher level than in the general population, is partially fulfilled. Several studies support that our data reveal a lower performance in PS among unaffected first-degree relatives compared with HC (Chu et al, 2019; Erzin et al, 2021; Feng et al, 2020; Valerio et al, 2021; Van Os et al, 2020; Voráčková et al, 2021). Last, the criterion (f), to be a reliably measurable trait that is more strongly associated with the specific disease of interest than with other psychiatric conditions, is partially fulfilled.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Criterion (e), impairment in affected and unaffected family members at a higher level than in the general population, is partially fulfilled. Several studies support that our data reveal a lower performance in PS among unaffected first-degree relatives compared with HC (Chu et al, 2019; Erzin et al, 2021; Feng et al, 2020; Valerio et al, 2021; Van Os et al, 2020; Voráčková et al, 2021). Last, the criterion (f), to be a reliably measurable trait that is more strongly associated with the specific disease of interest than with other psychiatric conditions, is partially fulfilled.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning criterion (b), the presence of a deficit in PS among firstdegree relatives reinforces the potential genetic association between cognitive deficits and familial heritability, as supported by the existing literature (Lichtenstein et al, 2009;Sullivan et al, 2003;Toulopoulou et al, 2007). Furthermore, our results showed that first-degree relatives are situated in an intermediate performance on PS between FEP patients and HC (Chu et al, 2019;Erzin et al, 2021;Feng et al, 2020;Valerio et al, 2021;Van Os et al, 2020;Voráčková et al, 2021). Regarding criterion (c), state independence, the cross-sectional nature of our study did not allow us to explore this circumstance.…”
Section: Tablesupporting
confidence: 60%
See 1 more Smart Citation
“…Zgodnie z oczekiwaniami pacjenci wykazywali zaburzenia we wszystkich domenach poznawczych. Pacjenci i rodzeństwo wykazywali podobny profil w każdym z podtypów, w nasileniu upośledzenia i wzorcach funkcjonowania poznawczego [17]. Drugie z badań z 2020 roku dotyka zaburzeń funkcji poznawczych osób, które przebyły pierwszy epizod schizofrenii oraz ich zdrowego rodzeństwa w kontekście poznania społecznego, o czym poniżej [18].…”
Section: Badanie Chorych Z Pierwszym Epizodem Psychozyunclassified
“…Various works on this topic have confirmed that more than 80% of patients with schizophrenia suffer from various degrees of cognitive deficit, which markedly influence daily functioning 14 , 16 18 . Cognitive impairment can be detected before the appearance of first-episode symptoms (at prodromal state) and to some extent also in the first degree of healthy relatives 27 , 28 . A deficit of cognitive performance can be found in several neurocognitive domains and also in social cognition in schizophrenia patients 14 .…”
Section: Introductionmentioning
confidence: 99%